ACTH depresses delta 6 and delta 5 desaturation activity in rat adrenal gland and liver - Mandon, Elisabet C. (1987)
The in vivo and in vitro effect of ACTH on the biosynthesis of polyunsaturated fatty acid of rat adrenal gland and liver was studied. The administration of ACTH to intact rats produced a significant decrease in the conversion of [1-14C]linoleic acid to gamma-linolenic acid, [1-14C]alpha-linolenic acid to octadeca-6,9,12,15-tetraenoic acid, and [1-14C]eicosa-8,11,14-trienoic acid to arachidonic acid in liver and adrenal microsomes. Isolated adrenocortical cells and hepatocytes obtained from animals treated with ACTH showed a decrease in the incorporation and desaturation of exogenous [1-14C]eicosa-8,11,14-trienoic acid. The addition of ACTH to the incubation medium of adrenocortical cells and hepatocytes isolated from untreated rats also caused a decrease in delta 5 desaturation activity. The effect of ACTH on adrenal and liver desaturases could be produced as a consequence of the release of glucocorticoids, already measured in the experiments. However, the in vitro experiments carried out with hepatocytes isolated from untreated rats, where corticosterone was absent, indicated that ACTH can depress delta 5 desaturation per se.